The burden of invasive infections in neutropenic patients: incidence, outcomes, and use of granulocyte transfusions (Editorial, p. 6). Issue 1 (1st November 2018) - Netelenbos, Tanja; Massey, Edwin; de Wreede, Liesbeth C.; Harding, Kay; Hamblin, Angela; Sekhar, Mallika; Li, Anna; Ypma, Paula F.; Ball, Lynn; Zwaginga, Jaap Jan; Stanworth, Simon J.
Abstract : BACKGROUND: Patients with prolonged neutropenia caused by chemotherapy or underlying marrow disorders are at risk of invasive bacterial and fungal infections. New treatment options alongside targeted antimicrobial therapy that might improve outcomes include granulocyte transfusions (GTX). To inform the research agenda, a prospective observational cohort study was performed in the Netherlands and United Kingdom. The aim was to describe the incidence, characteristics, and outcomes of patients developing invasive infections and assess patients fulfilling criteria for GTX. STUDY DESIGN AND METHODS: All patients receiving myeloablative chemotherapy and anticipated to develop 7 or more days of neutropenia (<0.5 × 10 9 /L) were eligible and followed for the development of invasive infections according to a defined algorithm and mortality up to 100 days. Secondary outcomes were types of infection and eligibility for GTX. RESULTS: A total of 471 patients enrolled at six hematology‐oncology departments were followed for 569 neutropenic episodes. Overall, 32.5% of patients developed invasive infections during their first episode. Significant baseline risk factors for developing infections were high comorbidity scores (WHO performance status ≥ 2, hazard ratio [HR], 2.6 [1.7‐3.9]; and hematopoietic cell transplantation‐comorbidity index score ≥ 2 HR 1.3 [0.9‐1.8]). Infections were bacterial (59.4%) and fungal (22.3%). Despite 34 patients (6.3% of all episodes) appearing to meet criteria to receive GTX, only nine patients received granulocytes. The HR for death was 5.8 (2.5‐13.0) for patients with invasive infections. CONCLUSION: This study documents that invasive infections are associated with significant mortality. There is a need for new strategies to prevent and treat infections, which may include better understanding of use GTX.